Pengaruh Tata Kelola Perusahaan Terhadap Performa Bank yang Terdaftar di Otoritas Jasa Keuangan - Juliani, Meily; Jennica (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
This study aims to investigate the effect of the characteristics of board of commissioners on bank performance which measured by ROA and PAT in banking companies listed on the Financial Services Authority for period 2017-2021. The characteristics of the board of commissioner consist of the board size, independent commissioner, board of commissioner meeting, and board of commissioner expertise. The population of this study was banking companies listed in the Financial Services Authority in period 2017-2021 with a total sample of 312 data. This study used the panel regression method and showed that the variable board size has a significant positive effect on PAT and does not have a significant effect on ROA. The independent commissioner, board of commissioner meetings, and board of commissioner expertise also have no significant effect on bank performance.